If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 119 + -3x = 5x + 15 Reorder the terms: 119 + -3x = 15 + 5x Solving 119 + -3x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 119 + -3x + -5x = 15 + 5x + -5x Combine like terms: -3x + -5x = -8x 119 + -8x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 119 + -8x = 15 + 0 119 + -8x = 15 Add '-119' to each side of the equation. 119 + -119 + -8x = 15 + -119 Combine like terms: 119 + -119 = 0 0 + -8x = 15 + -119 -8x = 15 + -119 Combine like terms: 15 + -119 = -104 -8x = -104 Divide each side by '-8'. x = 13 Simplifying x = 13
| -28=-6x+26 | | lg(lg(x))=0 | | v+x=w+w | | -43+6x=12x+65 | | x^3-5x^2-26x+120=0 | | x+x+(2x-5)+(2x-5)=38 | | -1(5-6x)=4(5x+3) | | -153+7x=-3x+57 | | 56+3x+4=8x | | -(5-6x)=4(5x+3) | | -10-10x=11-11x | | 9+9+(x+6)+(x+6)=52 | | -189-8x=4x+75 | | 2x+12=4(x-5) | | -110+2x=8x+70 | | -39+9x=12x+12 | | (X+3)+(X+3)+(X+3)+(X+3)=28 | | -40-3x=17-6x | | -63-10x=22-5x | | 5(d+8)+3(d-6)= | | 14/12=d/48 | | X^2-2=30 | | 10x-87=2x+49 | | -n=-2n | | 6z-3+8z-5=12z-4-2z-2 | | -5(2x-4)-(7x+5)+11x=-274 | | 1.2=2 | | -3x+2=1-3x | | 4.6=4m-3 | | 2x-69=6x+47 | | 4x^2-23x+120=0 | | -5(-6-7)+24=89 |